Sustainable Development Goals (SDGs): Economic Transformation Towards Sustainable Development - Iswanto, Dedy (Journal of Economic Growth and Development Review, 2024)
Sustainable Development Goals (SDGs) have become a crucial global framework in encouraging economic transformation towards sustainable development. This article examines how the SDGs agenda influences economic paradigm changes in various countries, as well as the challenges and opportunities that arise in the implementation process. Through analysis of comparative case studies from several countries, this research identifies key strategies and best practices in aligning economic policies with sustainable development goals. Key findings show that successful economic transformation depends on cross-sector policy integration, technological innovation, active involvement of the private sector, and strong international cooperation. The COVID-19 pandemic has also highlighted the importance of building a more resilient and adaptive economic system. Despite significant progress, implementation gaps remain a major challenge, especially in terms of financing and capacity development. This article concludes that achieving the SDGs requires a fundamental transformation in the way we understand and manage economic development, with an emphasis on a holistic approach that balances economic growth, social inclusion and environmental sustainability. The implications of this research highlight the need for accelerated efforts and policy innovation to realize the vision of sustainable development promoted by the SDGs.